Transcriptomic Analyses Reveal Light-Induced Anthocyanin Accumulation in Lycium ruthenicum Murray - Chen, Shengrong; He, Tao; Gu, Wenyi; Li, Ruimin; Qi, Yinyan (Horticulturae, 2025)
Light plays a crucial role in anthocyanin biosynthesis and color development in plants. Anthocyanins found in Lycium ruthenicum Murray are crucial for the plant’s defense against UV light and environmental stress, as well as for their economic value in functional foods and nutraceuticals due to their high antioxidant content. Despite this, the molecular mechanisms underlying this process remain incompletely understood. This study explores the molecular mechanisms that drive light-regulated anthocyanin accumulation in L. ruthenicum berries by conducting shading treatments and analyzing the transcriptomic data. Results indicated that shading from 5 to 25 days post-flowering greatly impedes the synthesis of anthocyanin, even if light exposure is increased afterward. This suggests that the early stages of fruit development are crucial for anthocyanin accumulation. In regular lighting conditions, a total of 22 anthocyanin types were detected, with Delphinidin-3-O-(p-coumaroyl)-glucoside (611) and Petunidin-3-O-rutinoside (933) being the most prevalent. When berries were exposed to early light, there was a greater presence of Petunidin-3-O-rutinoside (933), resulting in a black appearance, whereas those not exposed had a lighter color with higher levels of Delphinidin-3-O-(p-coumaroyl)-glucoside (611). RNA-Seq analysis showed a notable decrease in the expression of genes involved in the anthocyanin biosynthesis pathway (such as CHS, CHI, F3H, F3′H, F3′5′H, DFR, and ANS) following shading. Key regulatory genes like GRAS, HD-ZIP, MADS, and mTERF were involved in anthocyanin accumulation in response to light. A proposed model has been developed to elucidate the mechanism by which light controls the biosynthesis of anthocyanin, providing insights into light signal regulation. Our findings provide data to improve the understanding of light-induced anthocyanin accumulation in L. ruthenicum berries.